Asymmetric reactions in the tourism‐led growth hypothesis. (29th June 2022) - Kumar, Nikeel Nishkar; Patel, Arvind; Kimpton, Sean; Andrews, Antony
Abstract: In this study, we test for asymmetries in the tourism‐led growth hypothesis. Asymmetric causality tests allow us to examine whether positive or negative changes in tourism cause growth. Our specification is based on an extended Solow growth model and draws from recent articles on tourism and growth. Using Tonga as a case study over the period 1981–2018, we find that tourism asymmetrically Granger causes economic growth. The magnitude of effects from the nonlinear ARDL model shows that economic growth is more sensitive to a downward movement compared to an upward movement in visitor arrivals.